PENINGKATAN KESADARAN MASYARAKAT MENGENAI PENTINGNYA TERTIB BERLALU LINTAS DI DESA SUTOPATI, KECAMATAN KAJORAN, KABUPATEN MAGELANG. - Jaduk Gilang Pembayun; Sukron Mazid; Satrio Ageng Rihardi (Swadaya: Indonesian Journal of Community Empowerment, 2019)
Legal awareness is self-awareness without pressure, coercion, or orders from outside to submit to applicable law. With the running of legal awareness in the community, the law does not need to impose sanctions. Sanctions are only imposed on citizens who have proven to be violating the law. One of the legal problems today is the low awareness of the legal community, resulting in many violations of the law. The methods used in community service activities are lectures, discussions, questions and answers and simulations, so that the activities can run without boundaries and boundaries between the community service team and the community. Likewise in the implementation of community service, the service team applies the lecture, discussion, question and answer and simulation methods and uses a contextual approach in providing counseling and briefing to the community about the impact it has on the mindset of society related to traffic order. Initially, legal awareness mostly revolves around the mindset that assumes that awareness in the community is a deciding factor as a law. With the socialization carried out by the community service team, citizens became more sensitive and concerned about the importance of orderly traffic so that eventually Good Citizenship was formed.